Stakeholder perceptions of a school food policy ten years on - Pettigrew, Simone; Talati, Zenobia; Sauzier, M.; Ferguson, A. (Cambridge University Press, 2018)
OBJECTIVE: To assess (i) the extent to which stakeholders have accepted and implemented a Healthy Food and Drink Policy for schools a decade after its introduction and (ii) any resulting implications for canteen profitability. DESIGN: Online survey distributed via electronic newsletter to school principals. SETTING: Western Australian public schools. SUBJECTS: Principals, teachers, canteen managers, and parents and citizens committee presidents (n 307). RESULTS: Large majorities of respondents reported that the policy has made the foods and drinks provided in schools healthier (85 %) and that the policy constitutes a good opportunity to teach children about healthy eating (90 %). Only small proportions of respondents felt it had been difficult to implement the policy in their schools (13 %) or that the policy fails to accommodate parents' rights to choose the foods consumed by their children (16 %). Most of the policy outcomes assessed in both the initial post-implementation evaluation (2008) and the 10-year follow-up evaluation (2016) demonstrated significant improvement over time. CONCLUSIONS: The study results indicate that comprehensive school food policies can favourably influence the foods and drinks provided on school premises and can be highly acceptable to key stakeholders, without adversely affecting profitability. The results are encouraging for policy makers in other jurisdictions considering the implementation of similar policies.